Pemanfaatan Aplikasi PLN Mobile Sebagai Sarana Komunikasi Digital dalam Upaya Meningkatkan Kualitas Pelayanan Pelanggan Di PT PLN (Persero) UP3 Surabaya Barat - Nur Awaliah, Agustin; Nirawati, Lia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
PT PLN (Persero) has the responsibility to serve the community's needs for electricity, so that every customer has the right to good service. One way that can be done to improve service quality in this digital era is to utilize digital communication, because digital communication can make it easier to convey information and speed up information between problem service officers and customers so that it can influence customer satisfaction. This research was carried out using a qualitative approach with library research data collection techniques (Library Research) with research sources derived from books, scientific journals, literature and publications. The conclusion of this research is that digital communication facilities via the PLN Mobile application are widely used by customers. This application can improve the quality of customer service. This can also provide effective communication options. However, there are several challenges in utilizing digital communication facilities such as the PLN Mobile application, namely the need for a larger server capacity to store data, there are some service personnel who are less skilled in using this application, and geographical location is an obstacle due to the weakening of the communication system.